Expanded spectrum of varicella disease and the need for vaccination in India - Padma Srikanth; Ilakkiya Arumugam; Seetha N. Jeganathan; Rithvik Ramesh; Lakshmi Narasimhan Ranganathan; Shanthi Vijayaraghavan (Human Vaccines & Immunotherapeutics)
Varicella vaccine was first licensed in Japan and South Korea in 1989 for use in healthy children and was introduced in US in 1995. So far, 29 countries have adopted varicella vaccine in their universal immunization program (UIP). No Asian country, India included, has adopted the varicella vaccine as part of their UIP. The extra-cutaneous sites for VZV diseases are central nervous system and gastrointestinal tract, the expanded disease spectrum includes vasculopathy, myelitis, inflammatory bowel disease, perforated ulcers, and gastritis. The actual disease burden of varicella is not known as most of the infected individuals may not visit the physician. The amplifiable VZV DNA will not always be detectable in cerebrospinal fluid (CSF) samples in protracted illnesses such as vasculopathies, but demonstrable anti-VZV IgG in CSF has diagnostic value. The World Health Organization (WHO) position paper 2014 recommends two doses of varicella and zoster vaccines in targeted population. In India, varicella vaccine is not included in the UIP due to the cost and the belief that lifelong immunity occurs following primary infection. The expanded spectrum of VZV disease and the mounting body of evidence, however, suggest the need for both varicella and zoster vaccines in routine immunization schedule.